PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CANVA PADA DASAR DESAIN GRAFIS PESERTA DIDIK DI SMK - Harida; Hasanah Nur; Anas Arfandi (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study aims to: (1) to determine the results of the development of canva-based learning media at SMKN 5 Bone, and (2) to find out the development of canva-based learning media developed to meet valid, practical and effective criteria. This research uses Research and Development research methods carried out at SMKN 5 Bone. The research data was obtained by giving questionnaires to 34 respondents. Data analysis techniques used percentage descriptive analysis. The test results show that Canva-based learning media is easier and more practical to use in making designs. For system developers Data collection techniques through questionnaire collection to measure basic graphic design learning outcomes./1The validity of Canva-based media is assessed by media experts and content experts. The results of the media validation test show that canva-based learning media can be categorized as valid with a validity level by media experts of 3.86 and content experts of 3.42. Practical test of learning media by students amounted to 82% with a very practical category. Thus the resulting media can be declared very valid and practical to be used as learning support media.